Filosofía del derecho como modelo jurídico - Arturo Dorado, Néstor Raúl (2023)
This essay refers to the relevance of philosophy of law as a legal and philosophical model for the teachability of law and the education of modern legal ways of thinking. Philosophy of law is understood as a ―new methodology in phil osophical reflection about law.‖ Based on these premises, this paper starts by criticizing the way we have traditionally taught Roman law. According to the author, teaching this subject has become determinant, not only theoretically, but also ideologically , in the conservative character of most of Colombia‘s legal thought. Finally, the author refers to the usefulness of philosophy of law as a privileged space for the reading and rereading of schools of legal thought, such as natural law, positivism (in its different forms) and legal realism, starting with its trilemmic component of legitimacy, validity, and efficacy.